Identifikasi masalah kesehatan masyarakat di Desa Banguntapan melalui Data Program Indonesia Sehat Pendekatan Keluarga (PIS-PK) - Solikhah, Solikhah; Nuraisyah, Fatma; Ruliyandari, Rochana (Jurnal Cakrawala Promkes, 2021)
Noncommunicable diseases and chronic diseases, such as stroke, hypertension and diabetes mellitus has widely founded in Yogyakarta. In order to, the government has developed a health promotion strategy is the healthy Indonesia through a family program approach or Program Indonesia Sehat dengan Pendekatan Keluarga (PIS-PK). The study aimed to analysis determinant factors of public health problems, to obtain of the health situation and public health service in Ponegaran Hamlet, Banguntapan, Bantul. Descriptive research used to interview instruments as 149 respondents. The analysis method used to determine the priority of health problems is Urgency, Seriousness, Growth(USG). Base on three indicators of PIS-PK which were the main problems were the number of family members who smoker (53%), hypertension who did not take regular medication (71%) and health insurance (34%).